Estimated visceral adiposity is associated with risk of cardiometabolic conditions in a population based study - Maria Ruiz-Castell; Hanen Samouda; Valery Bocquet; Guy Fagherazzi; Saverio Stranges; Laetitia Huiart (Scientific Reports, 2021)
Abstract Visceral adiposity is a major risk factor of cardiometabolic diseases. Visceral adipose tissue (VAT) is usually measured with expensive imaging techniques which present financial and practical challenges to population-based studies. We assessed whether cardiometabolic conditions were associated with VAT by using a new and easily measurable anthropometric index previously published and validated. Data (1529 participants) came from the European Health Examination Survey in Luxembourg (2013–2015). Logistic regressions were used to study associations between VAT and cardiometabolic conditions. We observed an increased risk of all conditions associated with VAT. The total adjusted odds ratio (AOR, [95% CI]) for hypertension, prediabetes/diabetes, hypercholesterolemia, and hypertriglyceridemia for the fourth quartile of VAT compared to the lowest were (10.67 [6.95, 16.39]), (6.14 [4.14, 9.10]), (6.03 [3.97, 9.16]) and (9.18 [5.97, 14.12]). We observed higher odds in women than in men for all outcomes with the exception of hypertension. Future studies should investigate the impact of VAT changes on cardiometabolic health and the use of anthropometrically predicted VAT as an accurate outcome when no biomedical imaging is available.